Pengaruh Penggunaan Alat Peraga dari Bahan Bekas tentang Sistem Peredaran Darah pada Manusia Terhadap Hasil Belajar Biologi Siswa Kelas XI SMA Negeri 7 Kota Kupang Tahun Ajaran 2014/2015 - NOMLENI, FRANSINA TH.; MERUKH, JAMES E. (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2014)
This study aims to determine the effect ofthe use of props from scrap material son the human circulatory system to the learning outcomes compared to the results of studying biology classes which were not taught using the media props in class XI SMAN 7 Kupang in the academic year 2014/2015. Problems encountered in the scholar teachers do not use visual media in learning process so the impact is on learning outcomes biology students who do not achieve KKM 70. The method used in this study is the experimental method by using quasi-experimental design. Data collection was performed by using the test results of pretest and posttest as well as documentation. Results of pretest and post test data were analyze dusing t test formula with two groups design. The results showed that there were differences in learning outcomes between classes that were taught by using media props circulatory system of scrap materials that the average value of the pretest value X=39.03 while the posttest value X=80.80 and classes that were taught by not using media props circulatory system of scrap materials pretest value Y=37.58 and posttest value Y=65.48. The difference between the two classes of learning outcomes is also indicated by the results of the calculations to test the hypothes is using the t-test the t value is 5.74, while t table is 2.000. Can be concluded that there is the effect of using props froms crap materials on the human circulatory system of the human circulatory systemina better effect on learning outcomes compared to biology student learning outcomes and students who were taught not use theme diapropsin class XI SMAN 7 Kupang in the academic year 2014/2015. So it is recommended to teachers and prospective teachers in order to teach the material of the human circulatory system can use visual aids blood circulation system of scrap materials and also both teachers and prospective teachers can make props of scrap materials in other subject matter.